Problematika Pendaftaran Merek Untuk Usaha Mikro, Kecil dan Menengah di Kota Batam - F.Yudhi Priyo Amboro (Journal of Judicial Review, 2019)
The growth of Micro, Small, and Medium Enterprises (MSMEs) in Batam City is quite significant every year, but it is not directly proportional to the awareness of MSME owners to register their brand. This study is purposed to reveal the problems that occur in brand registration for MSMEs in Batam City, and then giving a solution to solve the problematic deadlock that arises. This research is empirical juridical research. The author got research data, both primary and secondary, then processed them with a qualitative approach that was supported by deductive thinking. The results of this study are able to reveal the problem of brand registration for MSMEs in Batam City which become an obstacle, namely difficult to access the brand registration information, differences in brand registration information, there are not many brand registration officers, and problems regarding understanding to the need for MSME permits. The solution to these problems can be solved not only by the government but also by other parties involved, especially those who have the potential to disseminate the information concerning the registration of brands and MSMEs.